Semantic change of Hijab, Halal and Islamist from Arabic to English - Almarwaey, Amjaad Omar; Ummul K. Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper explores the interrelationship between culture, language and communication. English language has established a position for itself as a widely spoken language in the world in many aspects of people’s lives regardless of race, creed or religion. Many Islamic specific terms have been borrowed into English as a result of continuous contact between Muslims and English-speaking communities. This study analyzes the semantic change of three commonly used Islamic terms by English speakers in daily life: hijab, halal, Islamist, and their definitions in English dictionaries. It aims to investigate their definitions and explore their associated meanings both in dictionaries and language in use. The definitions of the terms were compared in two reliable English dictionaries, Collins English Dictionary (CED) and Oxford Learner’s Dictionary (OLD). A well-known Arabic dictionary, Al Mu‘jam Alwasıt Dictionary (AAD), was used for reference of the original Arabic meaning. The Intelligent Web corpus (iWeb) was used to provide information on the use of the examined terms in daily language, and the words they collocate with. The study adopts a semantic change framework for data analysis. Findings of the research suggest that all three terms have undergone semantic changes, and their new meanings in English do not include the extra levels of social and religious meanings as in the original Arabic language. In particular, the term Islamist has developed negative connotations. Language in use has a strong influence on connotations associated to culture-specific terms.